Twinning dynamics in nanoscale body-centered cubic tungsten. (November 2022) - Li, Xiyao; Zeng, Qi; Wang, Jiangwei
Abstract: The non-planar core structure of screw dislocations in body-centered cubic (BCC) metals strongly influences its twinning dynamics, resulting in a minimum embryo size of six-layers {112} planes and discrete three-layers thickening behavior. By considering the energetically-stable three-layers "zonal dislocation" as a unit of twinning front, we rationalize such discrete twinning behavior to the two units for twin embryo and one unit for growth, in consistent with the description of classical twinning theory. Graphical abstract: Image, graphical abstract